Informing one-to-one computing in primary schools: Student use of netbooks - Larkin, Kevin; Finger, Glenn (Australasian Journal of Educational Technology, 2011)
Although one-to-one laptop programs are being introduced in many schools, minimal research has been conducted regarding their effectiveness in primary schools. Evidence-based research is needed to inform significant funding, deployment and student use of computers. This article analyses key findings from a study conducted in four Year 7 classrooms in which students were provided with netbook computers as an alternative to more expensive laptop computers. Variable access was provided to students including computer to student ratios of one-to-one and one-to-two. Findings indicated that increased access to the netbook computers resulted in increases in computer usage by these students, compared with their minimal use of computers before the study. However, despite the increased access, actual computer usage remained limited. The article reports that factors contributing to the minimal use of computers included individual teacher agency, a crowded curriculum, and the historical use of computers. Implications for policy and practice are suggested.